High-Dose Vitamin D(3) Supplementation in Children and Young Adults with HIV: A Randomized, Placebo-Controlled Trial - Stallings, Virginia A. (Pediatr Infect Dis J, 2015)
BACKGROUND: Suboptimal vitamin D status is prevalent in HIV-infected patients and associated with increased risk of disease severity and morbidity. We aimed to determine 12-mo safety and efficacy of daily 7000IU vitamin D(3) (vitD(3)) vs placebo to sustain increased serum 25-hydroxyvitamin D (25(OH)D) and improve immune status in HIV-infected subjects. METHODS: This was a double-blind trial of perinatally- (PHIV) or behaviorally-acquired (BHIV) HIV-infected subjects (5.0–24.9y). Safety, 25(OH)D-related parameters, and immune status were assessed at baseline, 3, 6, and 12 months. RESULTS: Fifty-eight subjects enrolled (67% male, 85% African-American, 64% BHIV) and 50 completed with no safety concerns. In unadjusted analyses, there were no differences between randomization groups at baseline; at 3, 6, and 12 months, 25(OH)D was higher with supplementation than baseline and higher than with placebo (P<0.05). In adjusted mixed models, in the supplementation group, the fixed effect of 25(OH)D was higher (P<0.001). Percentage of naïve T helper cells (Th naïve%) were significantly (P<0.01) and T helper cells (CD4%) marginally (P<0.10) increased with supplementation in those taking highly active antiretroviral therapy (HAART), and RNA viral load was reduced (P ≤ 0.05). In exploratory linear models, change in 25(OH)D predicted RNA viral load at 3 and 12 months and CD4% at 3 months (P<0.05). CONCLUSIONS: Daily 7000IU vitD(3) for 12 months was safe in HIV-infected subjects and effective in increasing 25(OH)D. Supplementation improved in some clinically important HIV immune markers in subjects on HAART. Adjunct therapy with high-dose, daily vitD(3) for HIV-infected subjects and for those on/off HAART requires further investigation.